Rancang Bangun Sistem Informasi Inventory Barang Berbasis Web pada Konter +62 Luragung Kuningan - Nugraha, Yogi; Fazrin Nasrulloh, Sofhian (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Konter +62 in Luragung, Kuningan faces challenges in Inventory management, which is still conducted manually. This manual process, particularly in tracking smartphones based on their unique IMEI numbers, leads to time inefficiency, high risk of recording errors, and delays in report generation for decision-making. This study aims to design and assess the feasibility of a web-based Inventory Information System as a solution. The research method used is Research and Development (RnD) with the Rapid Application Development (RAD) model, which is iterative and user-centered. System testing was carried out in two stages: functionality testing using the Black-Box Testing method by an IT expert, and usability testing with four end-users using a Likert scale questionnaire. The functionality test results showed that 100% of the test cases ran successfully as expected. Meanwhile, the usability test resulted in an average score of 4.69 out of 5, categorized as